Morphological Analyses of Colorectal Adenocarcinomas in Japanese Familial Adenomatous Polyposis Patients - Yozo Suzuki; Fumio Ishida; Hideyuki Ishida; Hideki Ueno; Hirotoshi Kobayashi; Tatsuro Yamaguchi; Tsuyoshi Konishi; Yukihide Kanemitsu; Takao Hinoi; Yasuhiro Inoue; Naohiro Tomita; Kenichi Sugihara (Journal of the Anus, Rectum and Colon, 2022)
Objectives: This retrospective study was conducted to clarify the morphological characteristics of colorectal cancer (CRC) in Japanese familial adenomatous polyposis (FAP) patients. Methods: This study was carried out by the study group for FAP of the Japanese Society for Cancer of the Colon and Rectum. FAP patients who underwent surgical resection between 2000 and 2012 were included in the study. Results: Of the 303 patients enrolled, 119 patients without CRC were excluded. Of 523 lesions, 49 lesions with missing morphological information were excluded; hence, only 474 CRC lesions in 178 patients (328 superficial lesions in 122 patients and 146 non-superficial lesions in 92 patients) were included in the study. Depressed lesions accounted for 3.0% of superficial lesions and ulcerated lesions accounted for 84.9% of non-superficial lesions. The depressed superficial lesions were observed only in patients with sparse and attenuated FAP (P = 0.003). The age of the patients at surgery differed between the two groups, with patients with depressed superficial lesions being significantly older than those with non-depressed superficial lesions (P = 0.009). Moreover, the age of the patients at FAP diagnosis differed between the two groups, with patients with ulcerated non-superficial lesions being significantly older than those with protruded non-superficial lesions (P = 0.006). Conclusions: In patients with FAP, depressed superficial CRC lesions rarely developed but were detected in our study group, and ulcerated non-superficial CRC lesions were also present with similar ratios. Clinicians should pay attention to depressed superficial lesions during endoscopic surveillance of FAP patients.